Demonstration of LOTUS multiphysics BEPU analysis framework for LB-LOCA simulations. (December 2018) - Blakely, Cole; Zhang, Hongbin; Szilard, Ronaldo; Epiney, Aaron; Vaghetto, Rodolfo; Ban, Heng
Highlights: Description of the Multiphysics Best Estimate Plus Uncertainty (MP-BEPU) framework LOTUS. Uncertainty quantification of multiphysics simulations in LOTUS. Application of LOTUS to LB-LOCA simulations. Abstract: The LOCA Toolkit for U.S. light water reactors (LOTUS) currently under development at Idaho National Labs (INL) is a plug and play, multiphysics environment to be used in support of system level plant transient analysis. New proposed rule changes in LOCA safety regulations (10 CFR 50.46c) require the inclusion of cladding hydrogen content in the evaluation of equivalent cladding reacted (ECR) and peak cladding temperature (PCT). The potential for a future implementation of said rule change motivates the current development of a unique union of core design, system analysis, and fuel performance codes within a framework allowing for uncertainty quantification (UQ). A demonstration of LOTUS capabilities to address this potential need is performed with an integration of the core design code PHISICS, the fuel performance code FRAPCON, and the system analysis code RELAP5-3D. UQ is performed via Wilks' method to compute the one sided 95/95 confidence values of the aforementioned safety metrics. Results demonstrate the benefits of the Multiphysics Best Estimate Plus Uncertainty (MP-BEPU) methodology and provide useful visualization of the limiting cases.